Detección de ADN de pescado en piensos vegetales mediante una técnica de PCR en tiempo real - Martín de Santos, R.; Martín de la Torre, I.; García Lacarra, T. (Revista Complutense de Ciencias Veterinarias, 2008)
A quantitative polymerase chain reaction (PCR) assay using SYBR green detection system has been developed for detection of fishmeal in feedstuffs. The real-time PCR method combines the use of fish-specific primers that amplify a 87 bp fragment of the mitochondrial 12S ribosomal RNA gene from fish species, and universal primers that amplify a 99 bp fragment of the nuclear 18S ribosomal RNA gene from eukaryotic DNA. The PCR method developed was applied to fish tissues/oats binary mixtures demonstrating its suitability for the detection of fish DNA in mixtures containing as low as 0.1% of fish tissues.